A guide to teaching practice - Cohen, Louis; Manion, Lawrence (London : Routledge, 1989)
A Guide to Teaching Practice has long been a major standard for all students on initial teacher training courses. This new edition has been extensively revised and updated to take account of the many changes which have taken place both within the education system and within training courses, including: * school-based training, * the impact of information technology and the increasing concern for school effectiveness. As before, the book covers all the important basic skills and issues which students need to consider during their practice, such as planning, classroom organisation, behaviour mana.
Includes bibliographical references.
Keywords: Student teaching -- Great Britain; Teachers -- Training of -- Great Britain